The Role of Artificial Intelligence in Enhancing The Accuracy of External Audit Reports an Applied Study on Commercial Banks According to The FRS - Annon, Shehlaa Neamah; Neamah, Shurooq Mohammed (Research Parks Publishers, 2025)
The research aims to evaluate the impact of using artificial intelligence techniques on improving the quality and accuracy of external audit reports issued by Iraqi banks. To achieve this goal, the research followed a descriptive and analytical approach, with data collected using a questionnaire distributed to a sample of 200 auditors and accountants working in Iraqi commercial banks. The research reached a set of results, the most important of which is a positive relationship between the use of artificial intelligence technologies, such as machine learning and data analysis, and increased accuracy of audit reports. These technologies contribute to reducing errors and improving the quality of reports. However, the application of artificial intelligence faces some obstacles, most notably the lack of technological infrastructure and supporting laws that enable the effective use of these technologies. Based on these findings, the study recommends training auditors on the use of AI tools to enhance their skills and ability to leverage these technologies in their work. It also emphasizes the importance of developing a legal framework that supports the integration of technology into auditing processes.